PENGARUH PENGETAHUAN PAJAK, SIKAP RASIONAL, DAN GENDER TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI : (Studi pada Wajib Pajak Orang Pribadi PT Starlight Garment Semarang) - Yuniarti, Aulia Tri; Muid, Dul (Cahaya Ilmu Bangsa, 2025)
Tax are a major source of government revenue and play a significant role for the country. This study aims to examine the effect of tax knowledge, rational attitude, and gender on individual taxpayer compliance at PT Starlight Garment Semarang. The research uses quantitative method with data collected through an online questionnaires distributed to 82 respondents at PT Starlight Garment Semarang. Determination of the sample uses probability sampling technique wich gives each respondents an equal opportunities of being selected. The data analysis technique is multiple linear regression using SPSS 25 application. The result of the research show that the independent variable: tax knowledge has a significance value of 0,000 < 0,05, rational attitude has a significance value of 0,000 < 0,05, and gender has a significance value of 0,385 > 0,05 in relation to the dependent variable: taxpayer compliance. This research concludes that tax knowledge and rational attitude have a significant effect on the taxpayer compliance,while gender has no significant effect on the taxpayer compliance.